Living with Nature, Cherishing Language Indigenous Knowledges in the Americas Through History - Olko, Justyna; Radding, Cynthia (Springer Nature, 2024)
This open access book explores the deep connections between environment, language, and cultural integrity, with a focus on Indigenous peoples from early modern times to the present. It illustrates the close integration of nature and culture through historical processes of environmental change in North, Central, and South America and the nurturing of local knowledge through ancestral languages and oral traditions. This volume fills a unique space by bringing together the issues of environment, language and cultural integrity in Latin American historical and cultural spheres. It explores the reciprocal and necessary relations between language/culture and environment; how they can lead to sustainable practices; how environmental knowledge and sustainable practices toward the environment are reflected in local languages, local sources and local socio-cultural practices. The book combines interdisciplinary methods and initiates a dialogue among scientifically trained scholars and local communities to compare their perspectives on well-being in remote and recent historical periods and it will be of interest to students and scholars in fields including sociolinguistics, (ethno)history, linguistic anthropology, cultural studies and cultural anthropology, environmental studies and Indigenous/minority studies.